Pengaruh Pemberian Limbah Sereh Wangi Hasil Penyulingan Minyak Atsiri Sebagai Pakan Ternak Terhadap Penampilan Induk Sapi Bali - Nurhayu A; Warda Warda (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Research conducted at Gowa Experimental Field in Pa'bentengang Village, Bajeng District, Gowa South Sulawesi. The aim of research to determine the effect of Addition Citronella Waste (Cymbopogon nardus L.) Essential Oil Refining Results as Forage Against Bali Cattle Appearance. This study was designed in a Completely Randomized Design (CRD) using 18 breeding Bali cattle aged 36 months-48 months divided into 3 treatment feed: A (elephant grass 100% + distillates citronella waste 0% + concentrate of 2 kg / head / day), B (elephant grass 80% distillates citronella waste 20% + concentrate of 2 kg / head / day), C (elephant grass 60% + distillates citronella waste 40% + concentrate of 2 kg / head / day ). The results showed that the 1 ha area planted with citronella, the carrying capacity of the waste citronella distillates based on dry matter (DM) in the first and second year in a row is 4:07 UT and UT 12.5. Average consumption of dry matter (DM) during the study is 5.35; 5.28; 5 in a row for treatments A, B, C, whereas daily weight gain in the treatment of a maximum of 0.26 kg / head / day, perlakuam B at 0:24 kg / head / day and treatment C of 0.20 kg / head / day.Key word : Waste, citronella, feed, cattle